(untitled) (Heritage, 2020)
The aim of this paper is to present crime related to cultural heritage in the world, and to determine through theoretical analysis whether it is increasing or decreasing. Reading the literature, it was concluded that crime in the field of cultural heritage is growing, and that it is most common in economically and socially underdeveloped countries. The countries of South America and the Middle East are at the top in this type of crime. The Western world is the ultimate destination for antique smuggling.